Parasite Control by Utilizing Genetic Host Resistance - Surtijono Partoutomo (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
As a tropical country, Indonesia is a favorable environment for the development of various species of parasites, consequently parasites become one of biological constraints that is difficult to overcome, particularly in traditional livestock farming's. The conventional parasite control technique has not been successfully implemented in traditional fanning as it requires capital support, which is unaffordable by small-scale farmers. Nowadays, the conventional control technologies for some parasites are considered to be uneconomical by several countries. Other reasons are the decrease of the economic value of certain livestock products, the appearance of anthelmintic resistance problems, and the occurrence of environmental pollution due to the utilization of chemicals and drugs. They then shift to genetic host resistance approach . In Indonesia, the approach on parasite control based on genetic host resistance may be used as an alternative technique which is based on the genetic host resistance is applicable at least as one of alternative technologies in controlling parasites selectively. This technology is cheaper, environmentally acceptable, and in line with the sustainable agriculture concept. The mechanisms ofthe genetic host resistance and its application in the field are briefly discussed in this paper. Key words: Genetic host resistance, parasite, control